Pengaruh Literasi Ekonomi, Status Sosial Ekonomi Orang Tua dan Modernitas terhadap Perilaku Konsumsi Peserta Didik - Ridha Wahyuni; Tuti Supatminingsih; Inanna Inanna; Muhammad Hasan; Syamsu Rijal (Indonesian Journal of Social and Educational Studies, 2020)
The study aims to know the impact of economic literacy, the social status of parents and modernity on consumption behavior students class XI IPS SMA Negeri 1 Selayar. The study was categorized as quantitative work with a population of 96 students, and a samples of 96 students. Data collection is done with documentation and questionnaire technique. The analysis technique used is a descriptive analysis technique. Research shows that: (1) Economic literacy does not have a positive and significant impact on consumption behavior students class XI IPS SMA Negeri 1 Selayar. (2) The social status of parents has a negative and significant impact on consumption behavior students class XI IPS SMA Negeri 1 Selayar. (3) Modernity has a positive and significant impact on consumption behavior students class XI IPS SMA Negeri 1 Selayar.